CREATIVE EFFORT OF ERIN GRUWELL IN RICHARD LAGGRAVENESSE'S THE FREEDOM WRITERS MOVIE (2007): A PSYCHOLOGICAL APPROACH - SUSIANINGTYAS, DENI AYU (2011)
This research discusses the creative effort of the major character Erin Gruwell, in changing her students related with Adler's theory individual psychology and it aimes to analyze the structural elements of Richard Lagravenesse's The Freedom Writers movie such as character and characterization, plot, point of view, style and theme based on individual psychological perspective. This research is a qualitative research. The data are taken from document analysis. The object of the study is analyzing the structural elements of the movie and discusses creative effort of Erin Gruwell viewed from individual psychology perspective. The results of study show a close relationship between The Freedom Writer movie and individual psychological. It can be concluded that the character and characterization, setting, theme, plot, and cinematography, directly supports the theme within the analysis, means that on the movie the entire structural elements consist of the whole narrative and structural elements. The creative effort to support her strives such as: the first situation where, she starts to be expected by her students. By using a psychological approach Gruwell tries to make a close relationship with them, this is the way to control the student's atmosphere in class. Gruwell creates small celebration event for them because they have been succeeded to change.